1972
DOI: 10.1002/chin.197218201
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: AZOLE 87. MITT. RK. VON HYDROXYLAMIN MIT MESITYLOXID

Abstract: Mesityloxid (II) reagiert mit Hydroxylaminhydrochlorid in Gegenwart von Na‐methylat in Methanol nicht zum Isoxazolin (I), sondern neben den isomer Oximen (III) bzw. (IV) entsteht das Isoxazolin (V) und das Isoxazolidin (VI) (bzw. der Methyläther).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This group has the same position in compound 30a, since the signal of the carbon of the methylene group is located at the same field (¿ch2 = 45.6). Belly et al (1972) assigned the Z-configuration to their crystalline compound (compound 33a in our study), which is in agreement with the observed chemical shift of the proton borne by the hydroxyl group (¿oh = 10.29) as the other isomer, the liquid one, has a proton resonating at lower fields (¿oh -10.58). The study of the chemical shift for the proton on the vinyl part confirms this assignment since the values obtained (¿ = 5.62 for compound 32a and ¿h = 6.00 for compound 33a) correspond to the configurations trans-trans and trans-cis determined by Buczkowski and Plenkiewicz (1970) for those oximes, their trans-cis derivative being the Z-isomer.…”
Section: Resultssupporting
confidence: 89%
“…This group has the same position in compound 30a, since the signal of the carbon of the methylene group is located at the same field (¿ch2 = 45.6). Belly et al (1972) assigned the Z-configuration to their crystalline compound (compound 33a in our study), which is in agreement with the observed chemical shift of the proton borne by the hydroxyl group (¿oh = 10.29) as the other isomer, the liquid one, has a proton resonating at lower fields (¿oh -10.58). The study of the chemical shift for the proton on the vinyl part confirms this assignment since the values obtained (¿ = 5.62 for compound 32a and ¿h = 6.00 for compound 33a) correspond to the configurations trans-trans and trans-cis determined by Buczkowski and Plenkiewicz (1970) for those oximes, their trans-cis derivative being the Z-isomer.…”
Section: Resultssupporting
confidence: 89%
“…Formation hydroxyisoxazolidines in the reaction of enones and hydroxylamine was tested only by Belly (aliphatic enones, scheme 2) [28] and Mavrov and Firgang (aliphatic-aromatic enones, scheme 3). [5,29] Mavrov and Firgang tested several bases and only for NaOH observed the formation of 5-hydroxy isoxazolidine with low to moderate yield.…”
Section: Introductionmentioning
confidence: 99%
“…[1,5,[7][8][9] For the last fifty years, there have been few articles about the synthesis of hydroxyl isoxazolidines from unsaturated carbonyl compounds and hydroxylamine (or its derivatives/ analogs). [4,5,[17][18][19][20][21][22][23][24][25][26][27][28][29] The formation of 5-hydroxyisoxazolidines easily occurred in neutral pH at room temperature (in rather an anhydrous condition), few examples of 3-hydroxyisoxazolidines synthesis are also known, but only for benzohydroxyamic acid and its analogs (p-NO 2 , p-Br and 2,3,5-(CH 3 ) 3 ). Hydroxy isoxazolidines are rather unstable (decompose when exposed to light and upon heating) and undergo chain-ring tautomerism.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] If the isoxazolidine molecule contains complex functional nucleophilic substituents, qualitatively new structural possibilities appear because these functions participate in further transformations (Scheme 1). Intermolecular nucleophilic attacks of these fragments at the C=N polar bond contained in the linear structure can lead to repeated cyclization with the formation of new cyclic forms.…”
Section: Introductionmentioning
confidence: 99%